Mandatory form of crop insurance with state support: arguments for and against (Путеводитель предпринимателя, 2020)
The article discusses the arguments supporting and questioning the feasibility of introducing a mandatory form of Russian crop insurance with state support funds. Substantiate the author’s position on the establishment of a reserve fund for backup recovery widespread catastrophic damage in particularly adverse weather conditions for years, leading to a complete loss of acreage and yield.